Flow characteristics and separation control in a transitional twin air-intake. (March 2023) - Yadav, KrishnaKumar R; Jain, Anuj; Paul, Akshoy Ranjan
Ambient air is ingested into the engine of military aircrafts using the air-intake system within a limited space. The flow non-uniformity produced in the air-intake creates flow separation and total pressure loss due to the centerline curvature and area diffusion which eventually affects its performance. The current work discusses the performance of a transitional twin air-intake without and in presence of slotted synthetic jets. The synthetic jet is employed just before the inflection at a range of velocity ratio from 1 to 10 and found that for a velocity ratio of 4.0, the pressure distortion at the aerodynamic interface plane is found minimum. Hence, the other performance parameters are computed at that optimized flow condition. The outcome of the study reveal that the static pressure is recovered by 4.61%–6.64% while the total pressure loss is decreased by 59.28%–89.95% using optimized synthetic jets for a range of Reynolds numbers.